Relevance of plasma biomarkers to pathologies in Alzheimer’s disease, Parkinson’s disease and frontotemporal dementia - Chiu, Pai-Yi; Yang, Fu-Chi; Chiu, Ming-Jang; Lin, Wei-Che; Lu, Cheng-Hsien; Yang, Shieh-Yueh (Scientific reports, 2022)
Amyloid plaques and tau tangles are pathological hallmarks of Alzheimer’s disease (AD). Parkinson’s disease (PD) results from the accumulation of α-synuclein. TAR DNA-binding protein (TDP-43) and total tau protein (T-Tau) play roles in FTD pathology. All of the pathological evidence was found in the biopsy. However, it is impossible to perform stein examinations in clinical practice. Assays of biomarkers in plasma would be convenient. It would be better to investigate the combinations of various biomarkers in AD, PD and FTD. Ninety-one subjects without neurodegenerative diseases, 76 patients with amnesic mild cognitive impairment (aMCI) or AD dementia, combined as AD family, were enrolled. One hundred and nine PD patients with normal cognition (PD-NC) or dementia (PDD), combined as PD family, were enrolled. Twenty-five FTD patients were enrolled for assays of plasma amyloid β 1–40 (Aβ 1–40 ), Aβ 1–42 , T-Tau, α-synuclein and TDP-43 using immunomagnetic reduction (IMR). The results show that Aβs and T-Tau are major domains in AD family. α-synuclein is highly dominant in PD family. FTD is closely associated with TDP-43 and T-Tau. The dominant plasma biomarkers in AD family, PD family and FTD are consistent with pathology. This implies that plasma biomarkers are promising for precise and differential assessments of AD, PD and FTD in clinical practice.